Pengaruh Kepemimpinan Transformasional dan Kompensasi Finansial terhadap Kepuasan Kerja Karyawan pada PT. BPR JAYA KERTI di Kabupaten Badung - Ni Komang Ayu Aristiana Dewi; Made Yudi Darmita; I Putu Agus Suarsana Ariesta (Universitas Triatma Mulya, 2024)
The development of employee job satisfaction will affect their attitudes and enthusiasm at work so that company goals are achieved. The phenomenon in this study is how the influence of transformational leadership (X1) on job satisfaction (Y) of employees at PT. BPR Jaya Kerti in Badung Regency, how is the influence of financial influence (X2) on job satisfaction (Y) of employees at PT. BPR Jaya Kerti in Badung Regency, what is the effect of leadership transformation and financial compensation on employee job satisfaction at PT. BPR Jaya Kerti in Badung Regency and its independent variables that have a dominant influence on employee job satisfaction at PT. BPR Jaya Kerti in Badung Regency. The population in this study was 44 people and the sample in this study was 43 people. This study used simple random sampling. The data analysis technique used is quantitative analysis, research instrument test, classical assumption test, multiple linear regression analysis, t test analysis, determination analysis and dominant test. The conclusions obtained are leadership transformation (X1) which has a positive and significant influence on job satisfaction (Y) of employees at PT. BPR Jaya Kerti in Badung Regency, Financial compensation (X2) has a positive and significant influence on job satisfaction (Y) of employees at PT. BPR Jaya Kerti in Badung Regency. The magnitude of the influence of transformational and financial leadership on employee job satisfaction at PT. BPR Jaya Kerti in Badung Regency is 63.9% and the remaining 36.1% is influenced by other variables not examined in this study. The independent variable that has a dominant influence on job satisfaction can be seen in the value of Standardized Coefficients Beta, which is the transformational leadership variable (X1), which is equal to 0.444.